Histological Research and Phytochemical Characterization of Capsella bursa-pastoris Medik. from Bihor County, Romania - Sorina-Georgiana Onea (Minz); Annamaria Pallag; Cristina Burlou-Nagy (Fati); Tünde Jurca; Laura Gratiela Vicaș; Marian Eleonora; Neli Kinga Olah; Rita Kiss; Bianca Pașca (Life)
Capsella bursa-pastoris Medik. (CBP) is a species with antibacterial, anti-inflammatory, antioxidant, anticancer, and hepatoprotective effects. We have chosen to study this species because, although it is a common plant with a distinctive fruit appearance, its effects are not fully understood. The aim of this study was to characterize the histoanatomy of the vegetative, reproductive organs and to characterize CBP extracts in terms of bioactive compounds and its antioxidant capacity. This study investigated the quantitative chemical composition of this species using the HPLC method, revealing the total content in polyphenols, flavonoids, and anthocyanins, and investigated the antioxidant potential through fluorescence recovery after photobleaching (FRAP assay), cupric ion (Cu2+) reduction, (CUPRAC assay), and a free radical scavenging method (DPPH). Our results show that CBP is a rich source of flavonoids, mainly from the extract obtained from the fruits; it has an antioxidant capacity, with the highest values being obtained from mature flowers and ripe fruits. Of the active principles, the highest amounts, according to HPLC determinations, were obtained in flowers and are represented by hyperoside. Thus, we can recommend the studied species for phytopharmaceutical preparations.